Solvothermal synthesis of mesoporous manganese oxide with enhanced catalytic activity for veratryl alcohol oxidation - Jha, Ajay; Chandole, Tejansh; Pandya, Rajan; Roh, Hyun-Seog; Rode, Chandrashekhar V. (RSC Advances, 2014)
Catalyst activities of manganese and cobalt oxides prepared by solvothermal and co-precipitation methods were studied for veratryl alcohol oxidation. Manganese oxides showed higher activity performance than that of cobalt oxides irrespective of the method of preparation. The solvothermal method yielded mesoporous manganese oxide without using any template giving mixed phases of monoclinic Mn5O8 and hausmannite Mn3O4. The mesoporous manganese oxide exhibited excellent activity for liquid phase aerobic oxidation of veratryl alcohol under base free conditions, with 90% conversion and almost complete selectivity towards veratraldehyde. The detailed characterization results on morphology, size and composition of the prepared mesoporous manganese oxide obtained by XRD, XPS, H-2-TPR, N-2 adsorption-desorption isotherms, FESEM and HR-TEM techniques were used to understand the role of morphological and structural features in enhancement of the observed catalytic activity.

Influence of catalyst reduction temperature on autogenous glycerol hydrogenolysis over NiAl catalyst - Pandya, Rajan; Mane, Rasika; Rode, Chandrashekhar (Asian Journal of Organic Chemistry, 2022)
Autogenous glycerol hydrogenolysis to 1,2-propanediol by aqueous phase reforming (APR) was investigated over supported nickel catalysts. Effect of reduction temperature on physico-chemical properties of catalysts played a significant role in tuning conversion and product selectivities. The formation of nickel aluminate (NiAl2O4) spinel phase during catalyst reduction led to rearrangement of Ni species to obtain small and stable Ni particles. The catalyst activation temperature alters the extent of reduction of multivalent Ni species (Ni-0, Ni+2/+3) which facilitated glycerol dehydration and hydrogenation while suppressing C-C cleavage and thus avoiding undesirable side products. Additionally, presence of moderate Bronsted/Lewis acid ratio of the catalyst promoted higher 1,2-PDO selectivity. In-situ glycerol hydrogenolysis involves glycerol dehydration to acetol with simultaneous reforming to H-2 and CO2 and this hydrogen converts acetol to 1,2-PDO.
Keywords: APR; autogenous hydrogenolysis; Glycerol; Propanediols; reduction temperature; spinel